2020
DOI: 10.31234/osf.io/cbakz
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cooperation, Response Time, and Social Value Orientation: A Meta-Analysis

Abstract: Recent research at the cross between cognitive and social sci- ences is investigating the cognitive mechanisms behind coop- erative decisions. One debated question is whether cooperative decisions are made faster than non-cooperative ones. Yet em- pirical evidence is still mixed. In this paper we explore the implications of individual heterogeneity in social value orien- tation for the effect of response time on cooperation. We con- duct a meta-analysis of available experimental studies (n=8; treatments=16; 5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…In line with our expectations and previous studies [29,30,32], we observe that participants with higher prosocial attitudes behave more prosocial. While we find that self-reported intuitiveness has a positive effect on prosocial behavior in a bivariate analysis, this effect vanishes as soon as we control for prosocial attitudes.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In line with our expectations and previous studies [29,30,32], we observe that participants with higher prosocial attitudes behave more prosocial. While we find that self-reported intuitiveness has a positive effect on prosocial behavior in a bivariate analysis, this effect vanishes as soon as we control for prosocial attitudes.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, studies on this topic find that individuals with stronger prosocial attitudes act more prosocial. More interestingly, they also find evidence that prosocial individuals act less prosocial the longer they need to decide [29,30,32] and that similar results are observed when an experimental manipulation like time pressure is used [33].…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…Second, our previous studies have shown that the cultural background of players as well as their individual preferences may greatly affect the strategies players choose in coordination games [25,65,78]. For example, it was previously shown that highly prosocial participants and highly individualistic ones are fast responders (either they cooperate or defect, respectively) [79]. Hence, the effect of factors associated with both cultural differences and personal characteristics on the TBR and other electrophysiological indices should be further examined.…”
Section: Discussionmentioning
confidence: 99%
“… Mischkowski and Glöckner (2016) focused on social value orientation and argued that intuitive cooperation was observed for prosocials, but not for proselfs. In addition, Yamagishi and colleagues argued that only individuals with prosocial orientation may react intuitively and cooperatively ( Yamagishi et al, 2017 ; Andrighetto et al, 2020 ). These accumulating insights into intuitive cooperation, however, have not sufficiently examined the situational factors surrounding decision makers other than individual factors.…”
Section: Introductionmentioning
confidence: 99%